Specific and Nonspecific Interactions in Ultraweak Protein–Protein Associations Revealed by Solvent Paramagnetic Relaxation Enhancements - Johansson, Helle; Jensen, Malene Ringkjøbing; Gesmar, Henrik; Meier, Sebastian; Vinther, Joachim M; Keeler, Camille; Hodsdon, Michael E; Led, Jens J (Journal of the American Chemical Society, 2014)
Weak and transient protein–protein interactions underlie numerous biological processes. However, the location of the interaction sites of the specific complexes and the effect of transient, nonspecific protein–protein interactions often remain elusive. We have investigated the weak self-association of human growth hormone (hGH, K D = 0.90 ± 0.03 mM) at neutral pH by the paramagnetic relaxation enhancement (PRE) of the amide protons induced by the soluble paramagnetic relaxation agent, gadodiamide (Gd(DTPA-BMA)). Primarily, it was found that the PREs are in agreement with the general Hwang-Freed model for relaxation by translational diffusion (J. Chem. Phys. 1975, 63, 4017–4025), only if crowding effects on the diffusion in the protein solution are taken into account. Second, by measuring the PREs of the amide protons at increasing hGH concentrations and a constant concentration of the relaxation agent, it is shown that a distinction can be made between residues that are affected only by transient, nonspecific protein–protein interactions and residues that are involved in specific protein–protein associations. Thus, the PREs of the former residues increase linearly with the hGH concentration in the entire concentration range because of a reduction of the diffusion caused by the transient, nonspecific protein–protein interactions, while the PREs of the latter residues increase only at the lower hGH concentrations but decrease at the higher concentrations because of specific protein–protein associations that impede the access of gadodiamide to the residues of the interaction surface. Finally, it is found that the ultraweak aggregation of hGH involves several interaction sites that are located in patches covering a large part of the protein surface.